Children at samba school: the Ethnography's know-how in local contexts of education - Fabiana Duarte; Patrícia de Moraes Lima (Universidade Federal de Santa Catarina, 2019)
This text aims to reflect ethnography as a methodology that allows the construction of local knowledge with and about children. From the cultural and local practices in the context of the samba school, ethnography with children is problematized as a useful methodology and an epistemology that allows the production of knowledge recognizing children as subjects of rights who participate in collective interaction marked by intergenerationality. This is based on research carried out on Carnival in the city of Florianópolis /SC and, specifically, on the "Projeto Mirim de Casais Mestre Sala e Porta Bandeira" of the Embaixada Copa Lord Samba School, located in the Morro da Caixa community in the central region of the city, on what the proximity with the children and adults allowed to know the children's place within the existing practices there. In this text we choose to reflect on the improvement of ethnographic doing, identifying how time, relationships and the choice of "techniques" and resources occur in the research process with children, in an effort to intersect ethnography through the field of Anthropology, placing it in a dialogue with Childhood Studies and seeking to know children from the local contexts in which they constitute their ways of life.